Childbirth outcomes in rape-related pregnancies: a comparative study of women receiving care in a birthing room designed to promote person-centredness in eastern Democratic Republic of Congo - Urban Berg; Emile Mapatano; Maria Hogenäs; Marie Berg (Global Health Action)
Background There is limited knowledge regarding childbirth outcomes among women with pregnancies resulting from rape. At Panzi Hospital, a tertiary hospital in eastern Democratic Republic of Congo (DRC), a holistic care programme is provided for survivors of sexual violence. Objective Explore childbirth outcomes among women classified as Robson Group 1 who received care in a birthing room designed to promote person-centredness, comparing those with rape-related pregnancies to other women. Methods This study was conducted between March 2021 and July 2022, with consecutive collection of childbirth data from nulliparous women at term with a single foetus in cephalic presentation and spontaneous onset of labour, i.e. Robson Group 1. All participants received care in a new birthing room designed to promote person-centredness. Childbirth outcomes were compared between women with rape-related pregnancies (n = 159) and those without (n = 302). Results No statistically significant differences in childbirth outcomes were observed. Among women with rape-related pregnancies, 81.8% had vaginal births, compared to 83.4% in the comparison group. Caesarean section rates were 18.2% and 16.6%, respectively. The childbirth experience was rated positively by 80.5% of women in the rape-related pregnancy group and 84.8% in the comparison group with scores of 8–10 on the modified Visual Analogue Scale for Overall Childbirth Experience (VAS-OCE, 0–10). Conclusions Childbirth outcomes among women with rape-related pregnancies receiving care within a holistic programme were comparable to those of other pregnant women, when care was provided in a birthing room designed to promote person-centred care.